The Influence of Workload and Work Discipline on Employee Performance at The Regional Library Office of North Sumatra Province - Siregar, Marintan Romasi Novalina; Sagala, Maduma Sari; Bako, Evi Novalin (Global Insights in Management and Economic Research, 2025)
Introduction: Employee performance in public service institutions remains a critical concern, particularly regarding factors such as workload and work discipline. This study examined the influence of workload and work discipline on employee performance at the Regional Library Office of North Sumatra Province. Purpose of the study: This research aimed to determine the extent to which workload and work discipline influence employee performance, both partially and simultaneously. Materials and methods: A quantitative approach was employed with saturated sampling involving 68 employees. Data were collected through validated questionnaires using a Likert scale. Multiple linear regression analysis was conducted using SPSS version 22 to test the hypotheses. Results: The regression equation Y = 4.307 + 0.364X₁ + 0.510X₂ demonstrated that both workload (t = 3.132, p = 0.003) and work discipline (t = 4.099, p = 0.000) significantly influenced employee performance. Simultaneously, both variables showed a significant effect (F = 70.584, p = 0.000) with an adjusted R² of 0.675, indicating that 67.5% of performance variance was explained by these factors. Conclusions: Workload and work discipline significantly influence employee performance at the Regional Library Office of North Sumatra Province. Appropriate workload management and consistent discipline enforcement are essential for optimizing employee performance in public service institutions.